2002
DOI: 10.1021/bk-2003-0835.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Arsenic by Plants in Southwest England

Abstract: The literature concerning arsenic in soils and plants is reviewed briefly. The uptake of arsenic by a number of plants that colonize sites, contaminated by arsenic from past mining and smelting activities, is described. Plants growing on soil with high As were stunted and displayed a red coloration. Armeria martima operates an exclusion mechanism, with low root/soil concentration ratios. Uptake of arsenic from soil in Calluna vulgaris and Agrostis tenuis show weak correlations with Fe in soil and soil pH. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…4). As was found in most plants, its biochemical role is unclear (Farago et al 2003;Kabata-Pendias and Mukherjee 2007).…”
Section: As In Transplantation Studiesmentioning
confidence: 94%
“…4). As was found in most plants, its biochemical role is unclear (Farago et al 2003;Kabata-Pendias and Mukherjee 2007).…”
Section: As In Transplantation Studiesmentioning
confidence: 94%
“…These sources are estimated to have contaminated some 700 km 2 of soil in Devon and Cornwall (Abrahams and Thornton 4 ). Detailed studies of 13 contaminated and control areas reviewed by Farago et al 5 have identified particularly high concentrations in soils at sites associated with smelting at Roseworthy (range 815 to 161000 mg g 21 , Frizzell 6 ), Devon Great Consols (120-52000 mg g 21 , Kavanagh et al 7 ), Poldice (432-37600 mg g 21 , Farago et al 8 ) and the Tamar Valley (120-52600 mg g 21 , Kavanagh et al 11 ). In terms of health risks, the potential for human exposure in the home environment has been investigated by the chemical analysis of house dusts (Johnson, 9 and Elgahi 10 ) and of human urine (Kavanagh et al 12 ).…”
Section: Introductionmentioning
confidence: 99%